Multiple cockade nevi. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Cockade nevus consists of three concentric lesions as follows: a central common nevus, surrounded by a halo of non pigmented skin and finally by an external nevus ring, which is concentric to the previous other two. The central nevus can be junctional, compound or dermal. The latter can be pigmented (3, 5) or skin colored (6). The two external rings of cockade nevus are less variable. The same individual has a single cockade nevus or two or many, even thirty (4). Histologically, in the non pigmented intermediate ring there is a junctional nevus. The latter lacks pigment and inflammatory infiltrate. However, the immunohistochemical studies show that the epidermal melanocytes of the poorly or not pigmented intermediate ring are DOPA-positive, testifying their capability of synthesizing melanin. These findings confirm that the lack or scarcity of pigmentation in the intermediate ring is only due to a functional block of melanin synthesis (4) and not to a destruction of melanin or melanocytes. The presence of cockade nevi has been related to other problems such as heart malformations (2), juvenile diabetes and mainly spinal dysraphism (1).